2022
DOI: 10.1002/jmv.28281
|View full text |Cite
|
Sign up to set email alerts
|

Bovine lactoferrin inhibits SARS‐CoV‐2 and SARS‐CoV‐1 by targeting the RdRp complex and alleviates viral infection in the hamster model

Abstract: Breast milk has been found to inhibit coronavirus infection, while the key components and mechanisms are unknown. We aimed to determine the components that contribute to the antiviral effects of breastmilk and explore their potential mechanism. Lactoferrin (Lf) and milk fat globule membrane inhibit severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐related coronavirus GX_P2V and transcription‐ and replication‐competent SARS‐CoV‐2 virus‐like particles in vitro and block viral entry into cells. We conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 55 publications
(118 reference statements)
2
10
0
Order By: Relevance
“…In addition, as Lf is reported to attach to the ACE2 cell receptor used by SARS-CoV-2 to enter the cell, the components of the liposome may induce protein changes in cellular TMPRSS2, which is also involved in the entry of this virus [15]. The mechanism of action of Lf against SARS-CoV-2 is also explained by its direct interaction with the receptor binding domain (RBD) of the Spike protein [30,31] and its binding to heparan sulfate proteoglycans, thus preventing the early attachment phase [14]. In addition, some in silico studies showed that Lf also interacts with the transferrin receptor 1, which can be an alternative co-receptor for SARS-CoV-2 entry [31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as Lf is reported to attach to the ACE2 cell receptor used by SARS-CoV-2 to enter the cell, the components of the liposome may induce protein changes in cellular TMPRSS2, which is also involved in the entry of this virus [15]. The mechanism of action of Lf against SARS-CoV-2 is also explained by its direct interaction with the receptor binding domain (RBD) of the Spike protein [30,31] and its binding to heparan sulfate proteoglycans, thus preventing the early attachment phase [14]. In addition, some in silico studies showed that Lf also interacts with the transferrin receptor 1, which can be an alternative co-receptor for SARS-CoV-2 entry [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding antiviral activity, viruses such as herpes simplex virus type 1 (HSV-1), human immunodeficiency virus (HIV), human hepatitis C virus (HCV), human papilloma virus (HPV), respiratory syncytial virus (RSV), Sindbis virus, and Semliki Forest virus, among others, have also been proven to be highly sensitive to human and/or bovine Lf in vitro [8,9,11,12]-. In addition, previous studies have investigated the potential in vitro antiviral activity of bovine Lf (bLf) against SARS- CoV-1 [13] and SARS-CoV-2 [14]. In addition, some clinical trials have reported the efficacy of bLf against SARS-CoV-2 [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several ingredients derived from breast milk possess antiviral activities. LF inhibits various viruses, including enveloped viruses such as SARS-CoV-2 [ 26 , 27 ], human hepatitis C virus [ 28 ], human hepatitis B virus [ 29 ], HIV [ 30 ], herpes viruses [ 31 ], hantaviruses [ 32 ], and non-enveloped viruses such as human papillomavirus (HPV) [ 9 ], enterovirus 71 (EV71) [ 13 ], echovirus 6 [ 33 ], adenovirus [ 34 ], and feline virus [ 35 ]. Whey protein is a mixture of α-whey protein, immunoglobulins, serum albumin, LF, and lysozyme.…”
Section: Discussionmentioning
confidence: 99%
“…The virus then releases RNA into the cell cytoplasm, inducing the production of early viral proteins, the replication of genetic material and the production of late viral proteins, followed by the assembly of progeny virions and their release by exocytosis [ 96 , 97 ]. Recent data indicate the antiviral potential of human and cow’s milk directed against SARS-CoV-2 and similar viruses [ 98 , 99 ]. For example, although viral RNA was confirmed in the milk of mothers infected with the SARS-CoV-2 virus, no infectious viral particles were isolated from it [ 100 ].…”
Section: The Role Of Lactoferrin In Lung Diseasesmentioning
confidence: 99%
“…In addition, it inhibits viral RNA-dependent polymerase, preventing the formation of progeny viral particles. It is known that this polymerase, as well as a helicase and 3CL proteases, are highly conserved proteins that are essential for the normal replication cycle of coronaviruses [ 99 ]. The importance of LF as an immunomodulator during COVID-19 is also highlighted, and it has recently been shown that LF causes an increase in the expression levels of genes related to the cell’s immune response to viral infection, which can interrupt SARS-CoV-2 infection [ 101 , 102 ].…”
Section: The Role Of Lactoferrin In Lung Diseasesmentioning
confidence: 99%